Efektivitas Rendaman Bawang Merah (Allium cepa) dan Nutrisi Terhadap Hasil Hidroponik Pakcoy (Brassica rapa) : The Effectiveness of Shallot (Allium cepa) and Nutrients Soak on Pakcoy (Brassica rapa) Hydroponic Results - Herawati, Jajuk; Indarwati, Indarwati; Helmi, Raffiuddin (Journal of Applied Plant Technology, 2022)
Hydroponic cultivation systems are increasingly popular among urban communities with not large land. This cultivation can provide benefits and effectiveness for those who carry it out. The wick system is one of the simple hydroponics methods that is easy to do, because it is a passive hydroponic system. This study aims to find out how the effect of shallot solution to the growth and production of bok coy plants on hydroponic cultivation of the wick system. Hydroponics of the wick system is a hydroponic method of the axis system, which is the simplest because it uses the principle of water capillarity. Distribution of nutrient solution towards root using axis intermediaries. This study used a Randomized Group Design (RDG) with 12 experimental units and the Least Significance Different (LSD) with an error rate of 5%. The concentration of shallot solution added is P0 (0%), P1(20%), and P2 (30%). The results showed that the treatment of AB mix nutrition as a hydroponic medium has a tendency to have a better effect on the growth parameters and yield of Pakcoy plants. AB mix treatment had a significant effect on production parameters, namely total wet weight, upper wet weight, root wet weight, and dry weight. Provision of shallot soak at concentrations of 20% and 30% added to hydroponic media with AB mix nutrition has not been able to improve the growth parameters and yield of Pakcoy.